2019
DOI: 10.1021/acs.chemmater.9b00675
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Pt Thin Films Using Dimethyl (N,N-Dimethyl-3-Butene-1-Amine-N) Platinum and O2 Reactant

Abstract: Pt thin films, using the Pt precursor, dimethyl­(N,N-dimethyl-3-butene-1-amine-N)­platinum (DDAP, C8H19NPt), were deposited by atomic layer deposition (ALD). The growth characteristics of the Pt thin films were systemically investigated. A saturated growth rate was obtained with an increase in precursor and reactant pulse times, revealing the nature of the ALD self-limiting process. The growth rate increased with increasing deposition temperature and finally became saturated above 280 °C, showing a high growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…recently reported a GPC of 0.085 nm with DDAP precursor. [ 30 ] Therefore, the current Pt precursor indicated a better/faster growth kinetics (surface reactivity) compared to the others. However, the overall ALD process conditions (like vapor pressure and size of the Pt precursor molecule, deposition temperature, reactant, shape, and size of the reactor, working pressure, etc.)…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…recently reported a GPC of 0.085 nm with DDAP precursor. [ 30 ] Therefore, the current Pt precursor indicated a better/faster growth kinetics (surface reactivity) compared to the others. However, the overall ALD process conditions (like vapor pressure and size of the Pt precursor molecule, deposition temperature, reactant, shape, and size of the reactor, working pressure, etc.)…”
Section: Resultsmentioning
confidence: 93%
“…[ 22,23,25 ] The preparation of the hierarchically porous NC–CC substrate is already reported, and in the current investigation, we followed the same procedure. [ 22,24 ] ALD of Pt has been investigated by several authors, [ 26–30 ] however, the majority of the reports uses trimethyl (methylcyclopentadienyl) platinum [IV] (MeCpPtMe 3 ) as the Pt precursor, and oxygen as the reactant. [ 27,28 ] Further, depending on the type of reactants (O 2 , air, and O 2 –H 2 mixture), the deposition temperature varies from 200 to 300 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Among the many strategies in this line, one can enhance ECA by further increasing the ratio of surface platinum atoms that are catalytically active, for example, by optimizing catalyst geometry, especially given that ALD can be utilized to synthesize atomic scale catalyst down to single‐atom active sites. [ 73,74 ] With innovations on ALD chemicals, especially the Pt ALD precursors, [ 75,76 ] and deeper understanding and innovation of ALD deposition processes, [ 77,78 ] ORR activity normalized by mass or cost are expected to be improved further.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al reported that the highest growth rate for Pt thin films occurred in the temperature range 280 °C to 340 °C. At higher temperatures, the Pt precursor typically is more exothermic, which is enhanced the chemisorption between precursor and converting agent on surface-active sites of the substrate, resulting in a fast growth rate [ 47 ]. Battiston et al reported that the starting temperatures for Pt film deposition should be at least 240 °C and they divided the deposition temperatures range 240–300 °C in the presence of oxygen and 280–440 °C in the water vapor.…”
Section: Resultsmentioning
confidence: 99%